Comparative genomics provide a rapid detection of Fusarium oxysporum f. sp. conglutinans - Jian LING; Ji-xiang ZHANG; Feng ZENG; Yue-xia CAO; Bing-yan XIE; Yu-hong YANG (Journal of Integrative Agriculture, 2016)
Fusarium oxysporum f. sp. conglutinans (Foc) is the causal agent of Fusarium wilt disease of Brassica oleracea. A rapid, accurate, and reliable method to detect and identify plant pathogens is vitally important to integrated disease management. In this study, using a comparative genome analysis among Fusarium oxysporum (Fo), we developed a Foc-specific primer set (Focs-1/Focs-2) and established a multiplex-PCR assay. In the assay, the Focs-1/Focs-2 and universal primers for Fusarium species (W106R/F106S) could be used to detect Foc isolates in a single PCR reaction. With the optimized PCR parameters, the multiplex-PCR assay showed a high specificity for detecting Foc and was very sensitive to detect as little as 100 pg of pure Foc genomic DNA or 1 000 spores in 1 g of twice-autoclaved soil. We also demonstrated that Foc isolates were easily detected from infected plant tissues, as well as from natural field soils, using the multiplex-PCR assay. To our knowledge, this is a first report on detection Fo by comparative genomic method.